2021
DOI: 10.1097/aud.0000000000001076
|View full text |Cite
|
Sign up to set email alerts
|

Listening Difficulties in Children With Normal Audiograms: Relation to Hearing and Cognition

Abstract: Objectives: Children presenting at audiology services with caregiverreported listening difficulties often have normal audiograms. The appropriate approach for the further assessment and clinical management of these children is currently unclear. In this Sensitive Indicators of Childhood Listening Difficulties (SICLiD) study, we assessed listening ability using a reliable and validated caregiver questionnaire (the Evaluation of Children's Listening and Processing Skills [ECLiPS]) in a large (n = 146) and hetero… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
51
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(75 citation statements)
references
References 70 publications
7
51
0
Order By: Relevance
“…This shows that children with LiD have challenges in both the auditory and cognitive processing represented in the Cue and Advantage scores. In our cross-sectional study of Wave 1 data, TD children scored significantly higher only in the LiSN-S Low Cue and Talker Advantage scores (Petley et al, 2021). Interestingly, in the secondary analysis of Wave 3 participants in the current study, children with LiD scored lower in Low Cue and Talker Advantage only, similar to the prior study.…”
Section: Spatial Hearingsupporting
confidence: 83%
“…This shows that children with LiD have challenges in both the auditory and cognitive processing represented in the Cue and Advantage scores. In our cross-sectional study of Wave 1 data, TD children scored significantly higher only in the LiSN-S Low Cue and Talker Advantage scores (Petley et al, 2021). Interestingly, in the secondary analysis of Wave 3 participants in the current study, children with LiD scored lower in Low Cue and Talker Advantage only, similar to the prior study.…”
Section: Spatial Hearingsupporting
confidence: 83%
“…No significant correlations were observed between functional connectivity and sensory-dominant tasks (e.g, LiSN-S advantage scores and SCAN filtered words). However, significant correlations were observed between functional connectivity and more cognitive-dominant tasks, specifically speechin-noise and task switching which are more strongly dependent on language and executive function, respectively (Petley et al, 2021). Overall, the data are consistent with the hypothesis that children with LiD have primarily cognitive and language processing deficits.…”
Section: Contrastsupporting
confidence: 78%
“…Increased connectivity may thus be indicative of increased processing efficiency and/or suppression of a task-relevant network, in this case language. Note that the behavioural measures used here have been shown to be either little affected by age (audiogram: Hunter et al, 2021) or were standardized across age (ECLiPS, LiSN-S, SCAN and NIH toolbox; (Petley et al, 2021).…”
Section: Functional Connectivity: Brain and Behaviourmentioning
confidence: 99%
“…People with higher hearing thresholds can manifest hearing impairment, communication difficulties, etc., even within the normal range ( 64 , 65 ). It is of note that children with hearing impairment but normal audiograms have problems with cognitive processing ( 66 ). In this study, we found that children with abnormal or borderline SDQ total difficulties scores had higher hearing threshold at certain frequencies.…”
Section: Discussionmentioning
confidence: 99%